1990
DOI: 10.1209/0295-5075/13/4/010
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Quasi-Crystal Formation in Al-Cu-Mn Induced by Ball Milling

Abstract: The influence of the milling conditions on phase formation and structural transitions induced by ball milling has been studied for Al&umMn15 powders by X-ray diffraction and differential scanning calorimetry. Depending on the experimental conditions, an amorphous, a quasi-crystalline, or a crystalline phase can be obtained from the layered composite of the pure elements. The various phases can be transformed into each other by further milling at suitable milling intensity. Possible mechanisms are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…However, in the last few years, it has been reported that quasicrystalline alloys can also be prepared by mechanical alloying (MA) [4]. Studies on the Al-Cu-Fe system prepared by MA have been reported in a number of papers [5][6][7][8]. Asahi et al, in the composition Al 65 Cu 20 Fe 15 observed that the formation of the icosahedral phase (i-phase) directly by MA [5], whereas Eckert et al could produce it only after subsequent annealing [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the last few years, it has been reported that quasicrystalline alloys can also be prepared by mechanical alloying (MA) [4]. Studies on the Al-Cu-Fe system prepared by MA have been reported in a number of papers [5][6][7][8]. Asahi et al, in the composition Al 65 Cu 20 Fe 15 observed that the formation of the icosahedral phase (i-phase) directly by MA [5], whereas Eckert et al could produce it only after subsequent annealing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the Al-Cu-Fe system prepared by MA have been reported in a number of papers [5][6][7][8]. Asahi et al, in the composition Al 65 Cu 20 Fe 15 observed that the formation of the icosahedral phase (i-phase) directly by MA [5], whereas Eckert et al could produce it only after subsequent annealing [6]. V. Sirinivas et al have studied the i-phase development in mechanically alloyed Al 70 Cu 20 Fe 10 powder mixture [7].…”
Section: Introductionmentioning
confidence: 99%
“…Typical QC alloys include Al-Mn, Al-Mn-Si, 118 Al-CuMn 119 or Al-Mg-Cu. 120 Currently used as protective coatings 121 and in advanced steel alloys for medical applications, these materials have high hardness (low friction), excellent mechanical properties and high temperature stability.…”
mentioning
confidence: 99%
“…The experimental i.e. milling conditions play also an important role as it was shown by milling experiments with A1-Cu-Mn powders [7][8][9].Milling experiments, carried out with aluminium and other metal powders, were mainly performed in …”
mentioning
confidence: 99%
“…compositions with high energy, only the amorphous state could be achieved [12]. In the case of some alloy compositions a continuous transformation from one structure to the other was possible by the appropriate selection of the mechanical and thermal treatments [8].…”
mentioning
confidence: 99%